Stable water isotope data for the surface samples collected at the Allan Hills Blue ice area - Introne, Douglas; Kurbatov, Andrei V.; Mayewski, Paul A.; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2018)
Stable water isotope data for the surface ice samples (listed as point numbers coordinates provided) collected at the Allan Hills Blue ice area have been generated under a collaborative effort by the University of Maine Climate Change Institute (NSF Award#1443306) and Princeton University (NSF Award# 1443263). This data set contains stable isotope data (dD, d18O) of meltwater samples collected from the area(76.73165 to 76.73348 S, 159.35343 to 159.42112 E).